Neurological Evaluation of Severe Congenital Kyphosis With Compressive Myelopathy in 39 Patients With a Minimum 1‐Year Follow‐Up - Jiaqi Zhang; Yan Zeng; Weishi Li (Orthopaedic Surgery, 2025)
ABSTRACT Objective Congenital angular kyphosis with compressive myelopathy is a rare yet underreported neurologic emergency for spine surgeons. The study aimed to report the neurological outcomes of 39 patients with compressive myelopathy in congenital kyphosis (CK) and provide magnetic resonance imaging (MRI) features in these patients, identifying the potential prognostic factors. Methods This is a retrospective cohort study. From January 2010 to December 2022, 39 patients were diagnosed with severe congenital angular kyphosis with compressive myelopathy and received surgical correction. The American Spinal Injury Association (ASIA) Impairment Scale grades at admission and final follow‐up were recorded to measure neurological outcomes. A series of qualitative and quantitative parameters were evaluated on preoperative MRI by observers who were blinded to the clinical outcomes. According to the final status of neurological recovery, patients were divided into two groups and compared: Group E (patients with ASIA E) and Group N (patients with ASIA A, B, C, and D). Results At the final follow‐up, 79.5% of patients (31 cases) had improved neurological function and myelopathy symptoms. The average Cobb angle of kyphosis decreased from 78.4° to 20.1° after correction surgery. The duration of myelopathy in Group N was significantly longer than that in Group E (p = 0.038). T1‐weighted imaging (T1WI) signal hypointensity was presented in 35.9% (14/39) of patients, and T2‐weighted imaging (T2WI) signal hyperintensity was 69.2% (27/39). On average, these patients had a maximum canal compromise (MCC) of 52.2%, maximum spinal cord compression (MSCC) of 47.0%, and maximum transverse area compression (MTAC) of 49.1%. Compared to Group E, Group N showed greater MCC (p = 0.023), MSCC (p = 0.008), and MTAC (p < 0.001) at baseline, and was more likely to present T1WI hypointensity and T2WI hyperintensity. The cut‐off values of MTAC, MCC, and MSCC for fully neurological recovery were 47.1%, 46.7%, and 52.6%, respectively. Conclusion MRI indicators of poor prognosis in CK patients with compressive myelopathy included the presence of T1WI hypointensity, T2WI hyperintensity, and greater MCC, MSCC, and MTAC. It was suggested that early surgical intervention is critical to prevent irreversible cord injury, particularly in patients with MTAC > 47.1%.